Evaluation of a multiple breath nitrogen washout system in children. Issue 8 (28th May 2020) - Isaac, Sarah M.; Jensen, Renee; Anagnostopoulou, Pinelopi; Davies, Jane C.; Gappa, Monika; Latzin, Philipp; Saunders, Clare; Short, Christopher; Singer, Florian; Stanojevic, Sanja; Zwitserloot, Annelies; Ratjen, Felix
Abstract: Introduction: The multiple breath nitrogen washout (MBW) test offers a sensitive measure of airway function. In this study we aim to (a) assess the validity of the EasyOne Pro LAB (MBWndd ) in an in vitro lung model, (b) assess the feasibility, repeatability, and reproducibility of MBWndd and (c) compare outcomes with the Exhalyzer D (MBWEM ) and body plethysmography. Methods: In vitro, functional residual capacity (FRC) measurements were assessed using a lung model under quasi‐physiological conditions and compared to measured FRC. In vivo plethysmography and MBW were performed in a prospective study of children at two visits (n = 45 healthy; n = 41 cystic fibrosis [CF]). Bland‐Altman plots were used to compare agreement between FRC and lung clearance index (LCI) measurements. Results: In vitro FRCndd measurements were repeatable but lung volumes were underestimated (mean relative difference −5.4% (limits of agreement [LA] −9.6%; −1.1%), 95% confidence interval (CI) −6.27; −4.45). In vivo, compared to plethysmography, FRCndd was consistently lower (−19.3% [−40.5; 1.9], 95% CI [−23.9; −14.7]), and showed a volume dependency. LCIndd values were also higher in children with smaller lung volumes. The within‐test coefficient of variation of the FRCndd and LCIndd were 4.9% in health, and 5.6% and 6.9% in CF respectively. LCIndd was reproducible between‐visits (mean relative difference [LA] −3.7% [−14.8, −7.5; 95% CI −6.6; −0.73] in health [n = 17] and 0.34% [−13.2, 22.8; 95% CI −5.0; 5.69] in CF [n = 23]). When calculated using the same algorithm, LCIndd was similar to LCIEM in health. Conclusions: MBWndd measurements are feasible, repeatable, and reproducible, however, MBW‐derived outcomes are not interchangeable with MBWEM .